Another India : The Making of the World's Largest Muslim Minority, 1947-77 - Anil, Pratinav (London Hurst & Company, 2023)
Another India' tells the story of the world's biggest religious minority. Weaving together vivid biographical portraits of a wide range of Indian Muslims - elite and subaltern, secular and clerical, activist and apolitical - it brings the experience of the country's Muslims under a single focus; and, by throwing light on the Indian Muslim condition during the first thirty years of independence, reflects on the true character of democratic India.
Including Bibliography and Index
Keywords: India -- Muslims -- Muslims India History 20th century